Electronically Reconfigurable HM-SIW Band-pass Filter Based on New CSRR Design Using PIN Diodes - Boubakar, Hichem; Abri, Mehadji; Benaissa, Mohamed (Journal of Informatics and Mathematical Sciences, 2021)
In this paper, a novel and original reconfigurable half-mode substrate integrated waveguide (HM-SIW) band-pass filter (BPF) is proposed. The proposed BPF is composed of two different size new design complementary split-ring resonators to achieve the compact size, and two PIN diodes to achieve the reconfigurability. This filter can function in three different cases according to the ON/OFF combination states of the PIN diodes. The operating state can either be a dual-band-pass filter with resonant frequencies 2.5GHz and 3.6 GHz that have measured return loss (RL) less than -23 dB and -25 dB, respectively. Or it can operate as a single-band-pass filter in two other cases. The resonant frequency of the first is 2.6 GHz that has a measured RL of -20 dB, and for the second one, the resonant frequency is 3.35 GHz that has -35 dB as a measured RL. Moreover, the measured insertion loss (IL) is better than 1 dB for all the cases. The size of this filter design is 26.3mm x 12mm which makes it a very compact device considering that it functions in the S-band compared to publish work that targets the same frequency band.